PENGARUH PROFITABILITY, CAPITAL STRUCTURE DAN FIRM SIZE TERHADAP FIRM VALUE DENGAN INVESTMENT OPPORTUNITY SET SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-2024 - Alfa Ayu Miftakhul Jannah; Ika Wahyuni; Lita Permata Sari (Fakultas Ekonomi dan Bisnis, 2026)
The capital market serves as a funding source for companies and an investment medium for the public in financial instruments. The existence of the capital market aims to provide long-term capital sources for the business world while creating income distribution through public stock ownership. This study aims to analyze and test the influence of profitability, capital structure, and firm size on firm value with the investment opportunity set as an intervening variable in LQ45 index companies listed on the Indonesia Stock Exchange for the 2022-2024 period. This research is a quantitative study with a causal approach aimed at explaining the relationships between variables. The population in this study consists of companies listed in the LQ45 index during the observation period. The sampling technique was determined using a purposive sampling method. Data analysis and hypothesis testing in this study utilize Structural Equation Modeling – Partial Least Square (PLS-SEM). The results of the direct effect hypothesis testing using the SmartPLS 3.0 application show that capital structure and firm size have a significant effect on firm value. Profitability and the investment opportunity set were found to have no significant effect on firm value. Profitability, capital structure, and firm size also do not significantly affect the investment opportunity set. The results of the indirect effect test indicate that the investment opportunity set is unable to mediate the influence of profitability, capital structure, or firm size on firm value.